2017
DOI: 10.1101/178194
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

L(3)mbt and the LINT complex safeguard tissue identity in the Drosophila ovary

Abstract: Maintenance of cellular identity is essential for tissue development and homeostasis. At the molecular level, cell identity is determined by the coordinated activation and repression of defined sets of genes. Defects in the maintenance of the genetic programs required for identity can have dire consequences such as organ malformation and cancer. The tumor suppressor L(3)mbt was shown to secure cellular identity in Drosophila larval brains by repressing germline-specific genes. Here we interrogate the temporal … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…The tumor suppressor L(3)mbt was shown to secure somatic cellular identity in Drosophila ovaries and larval brains by repressing germline‐specific genes, including nanos. Given its well‐documented role in translational regulation, it is likely that the primary role of Nanos is to repress factors that promote somatic development rather than to actively promote germ cell development, akin to its recently reported role in C. elegans. Whether Nanos also has an independent role in actively promoting germ cell fate is less clear.…”
Section: Ontogeny and Organization Of Germplasmmentioning
confidence: 99%
“…The tumor suppressor L(3)mbt was shown to secure somatic cellular identity in Drosophila ovaries and larval brains by repressing germline‐specific genes, including nanos. Given its well‐documented role in translational regulation, it is likely that the primary role of Nanos is to repress factors that promote somatic development rather than to actively promote germ cell development, akin to its recently reported role in C. elegans. Whether Nanos also has an independent role in actively promoting germ cell fate is less clear.…”
Section: Ontogeny and Organization Of Germplasmmentioning
confidence: 99%
“…Not surprisingly, the molecular characteristics of Δmbt ‐OSC cells have been altered because of the modification. The cells phenocopied undifferentiated germ cells that accumulate in the mutant ovaries and ectopically express germline markers Aub, Vasa and AGO3 (Coux, Teixeira, & Lehmann, ; Ishizu et al, ; Saito et al, ; Sumiyoshi et al, ).…”
Section: Generating Drosophila Cell Linesmentioning
confidence: 99%
“…In line with this, pilot studies undertaken by Alexey Soshnev found that Rbp9, along with a number of other Su(Hw) repressed targets, becomes upregulated in a l(3)mbt temperature sensitive mutant line (SOSHNEV 2012). Similar to Su(Hw), loss of l(3)mbt specifically in the germline leads to increased egg chamber apoptosis (COUX et al 2018). Together, these studies suggest that L(3)mbt may be another candidate for facilitating Su(Hw) function.…”
Section: Hipp1 Is Not Required For Su(hw) Repressor Functionmentioning
confidence: 77%
“…Both complexes have been shown to repress developmental gene expression (GEORLETTE et al 2007;MEIER et al 2012). L(3)mbt, as part of the LINT complex, represses the expression of neuronal and testis specific genes in female germline cells (COUX et al 2018). Given the similarity of this function to that of Su(Hw) in the ovary (SOSHNEV et al 2013), L(3)mbt represents another candidate partner of Su(Hw) that might facilitate repression.…”
Section: Hipp1 Is Not Required For Su(hw) Repressor Functionmentioning
confidence: 99%